Pengaruh Kepemimpinan Terhadap Kinerja Pegawai Pada Kantor Badan Pertanahan Nasional Kabupaten Gowa - Fauzan, Muh Nur; Mahsyar, Abdul; Parawu, Hafiz Elfiansyah (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine the effect of leadership on employee performance at the Gowa Regency National Land Agency. Leadership is a determining factor in an organization or company. The type of research used is quantitative research. The data sources used in this study are primary data sources and secondary data. Data collection techniques using observation and questionnaires with the number of respondents 50 people. Respondent data were analyzed by simple linear regression using SPSS version 25 application.The results of this study indicate that the leadership at the Office of the National Land Agency of Gowa Regency got results of 89.3% which was classified as very good. The performance of employees get results of 88.5% which is also classified as very good. Then the results of the T test, the regression coefficient value for the Employee Performance Variable is 0.965 with a significance of 0.000 which is smaller than 0.05 indicating that leadership has a significant influence on employee performance.